The safety and efficacy of delayed surgery by simulating clinical progression of observable papillary thyroid microcarcinoma: a retrospective analysis of 524 patients from a single medical center - Shi, Liuhong; Le, Kehao; Qi, Haiou; Feng, Yibing; Zhou, Liang; Wang, Jianbiao; Xie, Lei (Frontiers in Oncology, 2023)
Objective: When active surveillance (AS) is developed in the patients with low-risk papillary thyroid microcarcinoma (PTMC), a medical center needs to ensure the delayed operation that is caused by PTMC clinical progression to have the same prognosis as that of immediate operation.The objective of this study was to investigate the efficacy of delayed surgery by simulating clinical progression (tumor size enlargement and appearance of lymph node metastasis) of PTMCs with AS in a single medical center.We retrospectively analyzed the response to therapy in 317 papillary thyroid carcinoma patients treated with total thyroidectomy and post-operative radioactive iodine ablation. They were classified into three groups according to tumor size (group A ≤0.5 cm; group B >0.5 cm and ≤1 cm; group C >1 cm and ≤1.5 cm) or two groups according to the presence (cN1) or absence (cN0) of the clinical lymph node (LN) metastasis. Groups C and cN1 were regarded as simulated clinical progression of observational PTMC and the operation for them was assumed to be "delayed surgery". However, Groups A, B and cN0 were regarded as no clinical progression and the operation for them was considered as immediate surgery.Results: There were no significantly differences in excellent response to therapy and recurrencefree survival not only among the group A, B and C, but also between the group cN0 and cN1. In other words, these insignificant differences were found between immediate and simulated "delayed" surgeries.For the PTMC patients suitable for AS, the oncological outcomes were also excellent even if surgery was delayed until after the presence of clinical progression, according to our clinical simulation. Furthermore, we consider that it was feasible for medical centers to assess the ability to implement AS for PTMC patients by retrospectively analyzing their own previous clinical data using the described simulation.